Germination Pattern of Four Soybean Varieties on Media Containing Al, Fe, and Mn - Timotiwu, Paul Benyamin; Ermawati, Ermawati; Lestari, Dyah Tri; Manik, Tumiar Katarina (Journal of Agricultural Studies, 2022)
Acid soils in Lampung contain a lot of Al, Fe, and Mn, which inhibit soybean growth and production. The study of seed germination is important since plant growth begins with seeds. The study aimed to determine (1) the viability of various local soybean seeds: Anjasmoro, Grobogan, Dena-1, and Devon-1 on Al, Fe, and Mn heavy metal media and (2) the highest effect of dissolved metals among Al, Fe, and Mn on the viability of soybean seeds. The research was conducted at the Laboratory of Seed and Plant Breeding, Faculty of Agriculture, the University of Lampung from November 2019 to March 2020. The research applied a randomized complete block design (RCBD) with three replications and the data were averaged and presented as bar charts and standard deviation. The experiments were evaluated based on germination variables including germination capacity, average seed germination time, primary root length of normal germination, and dry weight of normal seedlings.The results showed that Grobogan and Anjasmoro varieties had high resistance to dissolved metals Al, Fe, and Mn, followed by Dena-1 varieties while Devon-1 was the most susceptible. The fourth day of germination showed that Fe caused the highest damage to the seeds, followed by Mn and finally Al. Interestingly, on the fifth day of germination, dissolved metal Mn had the highest toxicity effect, followed by Fe and Al.